TRADISI SLUP-SLUPAN Akulturasi Islam dan Budaya Jawa di Rembang Jawa Tengah - Misbakhudin, Misbakhudin (Sabda: Jurnal Kajian Kebudayaan, 2016)
This article deals with Islamic guidence and the Javanese culture acculturated within the tradition of selametan which is named slup-slupan in Rembang, Central Java. There are several meaningful symbols on this tradition according to the Javanese people, that these meanings have been originally changed by the Islamic guidence. The study shows that Javanese culture has been well acculturated to the Islamic guidence in the tradition of slup-slupan in Rembang.Â